2019
DOI: 10.3390/md17070393
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Soluble Proteome and the Cytolytic Activity of Unbleached and Bleached Millepora complanata (“Fire Coral”) from the Mexican Caribbean

Abstract: Coral bleaching caused by global warming has resulted in massive damage to coral reefs worldwide. Studies addressing the consequences of elevated temperature have focused on organisms of the class Anthozoa, and up to now, there is little information regarding the mechanisms by which reef forming Hydrozoans face thermal stress. In this study, we carried out a comparative analysis of the soluble proteome and the cytolytic activity of unbleached and bleached Millepora complanata (“fire coral”) that inhabited reef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 148 publications
(203 reference statements)
2
24
1
Order By: Relevance
“…Out of the 66 marine natural products identified, 26 correspond to structures that were not previously reported. These 26 new chemical entities correspond to three aliphatic polyketides (1-3), one glycolipid (7), two diterpenes (15,16), two steroids (24,25), one triterpenoid saponin (40), and 17 conotoxins (49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Figure 15 displays the overall biogenetic distribution of the reported compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 66 marine natural products identified, 26 correspond to structures that were not previously reported. These 26 new chemical entities correspond to three aliphatic polyketides (1-3), one glycolipid (7), two diterpenes (15,16), two steroids (24,25), one triterpenoid saponin (40), and 17 conotoxins (49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Figure 15 displays the overall biogenetic distribution of the reported compounds.…”
Section: Discussionmentioning
confidence: 99%
“…From specimens of Conus spurius, collected in Isla Arena, Campeche state, were isolated and identified by reverse transcription polymerase chain reaction, seven conotoxins. Four of them belong to the T-1 conotoxin family, (18V) sr5a (59), (18T) sr5a (60), "extended" (61), and "hydrophilic" (62), which were reported in 2009 [34], and they are very similar to the conotoxin sr5a (53). The other three, reported in 2010, were the known conotoxin sr11a (56) already reported in 2007 [31] and the new conotoxins, sr11b (63) and sr11c (64) [35] (Figure 9).…”
Section: Conotoxinsmentioning
confidence: 99%
“…Despite the ecological importance of a fully functional venom delivery system, it is surprising how few studies have attempted to look at how bleaching may impact on the cnidae and/or venom of bleached photo-symbiotic cnidarians. Indeed, only six research papers within the literature have been found to meet the criteria of comparing the effects on bleaching on either the cnidom, venom profile or toxicity, either over time ( Hoepner et al, 2019 ), or as direct comparisons to an unbleached cohort ( García-Arredondo et al, 2011 ; Gundlach, 2018 ; Gundlach and Watson, 2019 ; Hernández-Elizárraga et al, 2019 ; Olguín-López et al, 2019 ).…”
Section: Effects Of Bleaching On Cnidarian Venom Ecologymentioning
confidence: 99%
“…Bleaching has been shown to not only impact on the cnidarian venom apparatus system, but to also compromise the ability of cnidarians to produce venom ( Hoepner et al, 2019 ), and also change the properties within the venom itself ( García-Arredondo et al, 2011 ; Hernández-Elizárraga et al, 2019 ; Hoepner et al, 2019 ). Bleaching resulted in the volume of lyophilized crude venom of E. quadricolor (Actiniaria), which was collected monthly over a period of five months, to reduce significantly with time ( Hoepner et al, 2019 ).…”
Section: Effects Of Bleaching On Cnidarian Venom Ecologymentioning
confidence: 99%
See 1 more Smart Citation